2017
DOI: 10.1017/s0033291717000241
|View full text |Cite
|
Sign up to set email alerts
|

Differences in executive functioning between violent and non-violent offenders

Abstract: Violent offenders show worse response inhibition compared to non-violent offenders, suggesting a more pronounced prefrontal deficit in violent offenders than in non-violent offenders.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
55
2
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 62 publications
(64 citation statements)
references
References 30 publications
6
55
2
1
Order By: Relevance
“…Results for each of the four conditions were almost similar in both groups. Although previously found in some studies [16][17][18], we did not detect differences in executive functioning in our sample. However, neither Barkataki, Kumari, Das, Hill, Morris, O'Connell et al [17] nor Enticott, Ogloff, Bradshaw and Fitzgerald [18] found differences between violent and non-violent offenders with schizophrenia on measures of inhibition (Stroop-like tasks).…”
Section: Executive Functioncontrasting
confidence: 88%
See 3 more Smart Citations
“…Results for each of the four conditions were almost similar in both groups. Although previously found in some studies [16][17][18], we did not detect differences in executive functioning in our sample. However, neither Barkataki, Kumari, Das, Hill, Morris, O'Connell et al [17] nor Enticott, Ogloff, Bradshaw and Fitzgerald [18] found differences between violent and non-violent offenders with schizophrenia on measures of inhibition (Stroop-like tasks).…”
Section: Executive Functioncontrasting
confidence: 88%
“…However, neither Barkataki, Kumari, Das, Hill, Morris, O'Connell et al [17] nor Enticott, Ogloff, Bradshaw and Fitzgerald [18] found differences between violent and non-violent offenders with schizophrenia on measures of inhibition (Stroop-like tasks). Meijers, Harte, Meynen and Cuijpers [16] did find such differences, but they did not investigate participants with schizophrenia. As suggested by Enticott, Ogloff, Bradshaw and Fitzgerald [18], these results could indicate that cognitive inhibition may be differently related to impulsivity in schizophrenia and non-schizophrenia populations.…”
Section: Executive Functionmentioning
confidence: 95%
See 2 more Smart Citations
“…The IQ-delinquency relation was robust and independent of race, social class, motivation, and impulsivity. Antisocial adults have been found to exhibit broad and pervasive impairments in various executive functions (Hancock et al, 2010), including attentional set-shifting (Bergvall et al, 2001), response inhibition (Meijers et al, 2017), and planning and visual memory (Dolan and Park, 2002); the relation between antisocial behaviors and executive deficits has been found to be robust and statistically significant in meta-analyses (Ogilvie et al, 2011) with medium to large effect sizes (Morgan and Lilienfeld, 2000).…”
Section: Introductionmentioning
confidence: 99%